Effectiveness of Amiodarone, Propafenone And Synchronized Electrical Cardioversion for Conversion of Atrial Fibrillation Paroxysm to Sinus Rhythm in Rigas Stradins University Hospital Department of Emergency Medicine - Tracevskis, M.; Pupkeviča, I.; Kalējs, O. (Clinical Medicine And Health Research Journal, 2023)
Introduction: Atrial fibrillation remains one of the major causes of stroke, heart failure, sudden death, and cardiovascular morbidity in the world. Its incidence increases with age and the presence of structural heart disease. Materials and methods: The retrospective analysis was performed on 127 patients over a period of three years (73 men, median age 62, range 37-75, and 54 women, median age 60, range 42-78) duration of atrial fibrillation 48 hours or less. Results: Efficiency of amiodarone i/v converting atrial fibrillation to sinus rhythm detected in 56 of 69 patients (81.2%). Efficiency of propafenone i/v converting atrial fibrillation to sinus rhythm detected in 26 of 33 patients (78.8%). Efficiency of electrical cardioversion was pronounced in 24 of 25 patients (96.0%). (p<0.001 compared to both amiodarone and propafenone). In case if atrial fibrillation duration is less than 8h propafenone is more effective and for atrial fibrillation with duration over 24h more effective is amiodarone. Efficacy of amiodarone and propafenone in converting atrial fibrillation paroxysm to sinus rhythm was almost the same. The effect of amiodarone was slightly superior that of propafenon. Conclusion: Amiodarone, propafenone, and electrical cardioversion all three options provide physicians with effective tools to restore sinus rhythm in patients with atrial fibrillation. Atrial fibrillation duration should be taken into account more often to choose an appropriate treatment in emergency department.